Global existence of solutions to a chemotaxis‐haptotaxis model with density‐dependent jump probability and quorum‐sensing mechanisms. (25th April 2018) - Xu, Tianyuan; Ji, Shanming; Mei, Ming; Yin, Jingxue
Abstract : In this paper, we first derive a new chemotaxis‐haptotaxis model of cancer invasion of tissue with density‐dependent jump probability and quorum‐sensing mechanisms, which is with degeneracy in diffusion. In the presence of generic logistic damping, we then prove the global existence of weak solutions. The approach adopted is the compactness analysis with Moser‐type iteration and artificial viscosity‐vanishing technique.